Radio studies of relativistic SN 2009bb. Issue Volume 9:Issue S296(2013) (29th January 2014) - Ray, Alak; Yadav, Naveen; Chakraborti, Sayan; Soderberg, Alicia; Chandra, Poonam
Abstract: A local sub-population of type Ib/c supernovae (stripped envelope SNe) with mildly relativistic outflows have been detected as sub-energetic Gamma Ray Bursts (GRBs) or X-ray Flashes (XRFs) and as radio afterglows without detected GRB counterpart. SN 2009bb belongs to the last class of objects. The long term radio observations with (J)VLA and GMRT of this SN map the dynamics of the relativistic ejecta characteristic of Central Engines associated with GRBs. We present here GMRT observations of this SN from October 2009 onwards.